Symbolic Participation in Village Budgeting: A Legal Analysis of Community Involvement in Tangkulowi Village - Yusuf , Moh.; Saliha, Retnadumila; Ikbal, Moh. (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study analyzes community participation in the preparation of the Village Revenue and Expenditure Budget (APBDes) from the perspective of village governance law. Law Number 6 of 2014 on Villages, as lastly amended by Law Number 3 of 2024, normatively positions community participation as a fundamental principle of democratic and accountable village financial management. Using a normative-empirical legal approach, this research was conducted in Tangkulowi Village, Kulawi District, Sigi Regency. The findings reveal that community participation in APBDes preparation tends to be symbolic. Although formal involvement occurs through deliberative forums, community influence on budget priorities and allocations remains limited. Aspirations from indigenous groups, youth, and women are not adequately reflected in planning and budgeting documents. This symbolic participation weakens the legal legitimacy of the APBDes and reduces accountability and community oversight of village financial management. The study concludes that community participation in APBDes preparation constitutes a legal issue directly related to the quality of village democracy and the legitimacy of village governance.